Non- or Minimally Displaced Distal Radial Fractures in Adult Patients: Three Weeks versus Five Weeks of Cast Immobilization—A Randomized Controlled Trial - Bentohami, A.; van Delft, E. A. K.; Vermeulen, J.; Sosef, N. L.; de Korte, N.; Bijlsma, T. S.; Goslings, J. C.; Schep, N. W. L. (Journal of Wrist Surgery, 2019)
Background Patients with non- or minimally displaced distal radial fractures, that do not need repositioning, are mostly treated by a short-arm cast for a period of 4 to 6 weeks. A shorter period of immobilization may lead to a better functional outcome.Purpose We conducted a randomized controlled trial to evaluate whether the duration of cast immobilization for patients with non- or minimally displaced distal radial fractures can be safely shortened toward 3 weeks.Materials and Methods The primary outcomes were patient-reported outcomes measured by the Patient-Related Wrist Evaluation (PRWE) and Quick Disability of Arm, Shoulder and Hand (QuickDASH) score after 1-year follow-up. Secondary outcome measures were: PRWE and QuickDASH earlier in follow-up, pain (Visual Analog Scale), and complications like secondary displacement.Results Seventy-two patients (male/female, 23/49; median age, 55 years) were included and randomized. Sixty-five patients completed the 1-year follow-up. After 1-year follow up, patients in the 3 weeks immobilization group had significantly better PRWE (5.0 vs. 8.8 points, p = 0.045) and QuickDASH scores (0.0 vs. 12.5, p = 0.026). Secondary displacement occurred once in each group. Pain did not differ between groups (p = 0.46).Conclusion Shortening the period of immobilization in adult patients with a non- or minimally displaced distal radial fractures seems to lead to equal patient-reported outcomes for both the cast immobilization groups. Also, there are no negative side effects of a shorter period of cast immobilization. Therefore, we recommend a period of 3 weeks of immobilization in patients with distal radial fractures that do not need repositioning.
Keywords: conservative treatment; distal radial fractures; wrist fractures; immobilization period